2020
DOI: 10.1038/s41419-020-03007-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel epigenetic regulation of circFoxp1 on Foxp1 in colon cancer cells

Abstract: Foxp1 is a tumor suppressor in colon cancer. However, circFoxp1 derived from Foxp1 is an oncogene. In this study, we aim to investigate the role of circFoxp1 in colon cancer and the regulatory mechanism between circFoxp1 and Foxp1. 78 human colon tumor tissues and the matched paracancerous tissues were collected. Quantitative polymerase chain reaction, immunohistochemistry, quantitative methylation-specific PCR, chromatin immunoprecipitation assay, CCK-8 assay, and Tumor xenograft in nude mice were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In colon cancer tissues, the expression of circFOXP1 and FOXP1 was negatively correlated. CircFOXP1 recruits DNMT1 to hypermethylated the promoter of FOXP1, thereby inhibiting the expression of FOXP1, and ultimately facilitating tumor progression in colon cancer 28 . In our previous study, we identified that circFOXP1 expression was remarkably upregulated in gallbladder cancer tissues and cells, and promoted tumor progression and the Warburg effect in GBC cells by regulating PKLR expression 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer tissues, the expression of circFOXP1 and FOXP1 was negatively correlated. CircFOXP1 recruits DNMT1 to hypermethylated the promoter of FOXP1, thereby inhibiting the expression of FOXP1, and ultimately facilitating tumor progression in colon cancer 28 . In our previous study, we identified that circFOXP1 expression was remarkably upregulated in gallbladder cancer tissues and cells, and promoted tumor progression and the Warburg effect in GBC cells by regulating PKLR expression 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that downregulation of the miR-34 family in OC is associated with more aggressive disease . FOXP1, a transcription factor, a known target of miR-34a, is identified as an oncogene that upregulated in several malignancies. Upregulation of FOXP1 correlated with chemoresistance in FIGO stage III serous OC and high cytoplasmic FOXP1 expression in EOC was associated with a higher tumor grade …”
Section: Discussionmentioning
confidence: 99%
“…CCK-8 assay was performed as described in our previous described ( 27 ). A CCK-8 kit was used for determining the cell viability of NCCIT and Tcam-2 cells after siRNA transfection according to the instructions.…”
Section: Methodsmentioning
confidence: 99%